Analisa Karakteristik Peminum Teh di Kota Bandung - Fernando Leonardo; Nur Imam Taufik; Dwi Rianawati (Jurnal Akuntansi, 2019)
The surplus of tea industries in Indonesia is predicted to reach 56.877 tons in 2020. The decrease in the value of exports and the increase of tea production with a low tea consumption level has been the cause of this phenomenon. One of the ways to prevent this from happening is by improving tea consumption level in Indonesia. This studyaims to determine the characteristics of tea drinkers in the city of Bandung which is one of the major cities in Indonesia. This study uses a descriptive method with a qualitative approach. The number of sample used was 350 tea drinkers in Bandung who were processed using cross tabulation analysis techniques. The results showed that tea drinkers in Bandung were consumers who were in the middle to upper category who were practical people who liked tea in a package with a fresh tea flavor but not too bitter, and refreshing. Keywords: Tea, Targeting, Consumers’ Characteristics